Modernization of Indonesian Criminal Law from the Perspective of Legal Certainty and Social Utility - Muhammad Fadly Abdina; Abdul Rahman Maulana; Ismaidar (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
The modernization of Indonesian criminal law constitutes an essential part of national legal reform efforts in responding to the development of modern society, technological advancement, and the dynamics of contemporary crime. Criminal law reform is not merely aimed at replacing the colonial legal system, but also at establishing a national legal system capable of ensuring legal certainty while providing social utility for society. This study aims to analyze the modernization of Indonesian criminal law from the perspectives of legal certainty and social utility, as well as to examine the challenges of its implementation within the national criminal justice system. The research employs a normative legal research method using statutory, conceptual, and philosophical approaches. The findings indicate that the modernization of Indonesian criminal law through the enactment of the new Criminal Code (KUHP) reflects a paradigm shift toward a more adaptive, humane, and socially justice-oriented criminal law system. Nevertheless, various issues remain in its implementation, particularly concerning the balance between legal certainty and social utility. Law enforcement that is excessively formalistic often neglects aspects of social benefit and the public sense of justice, whereas an overly flexible approach may create legal uncertainty. Therefore, the modernization of Indonesian criminal law should be directed toward the establishment of a balanced and responsive legal system capable of addressing the challenges of contemporary developments without disregarding the fundamental principles of the rule of law.